Hearing Loss in Id1−/−; Id3+/− and Id1+/−; Id3−/− Mice Is Associated With a High Incidence of Middle Ear Infection (Otitis Media) - Zheng, Qingyin; Zheng, Tihua; Zhang, Aizhen; Yan, Bin; Li, Bo; Zhang, Zhaoqiang; Zhang, Yan (Frontiers in Genetics, 2021)
Inhibitors of differentiation/DNA binding (Id) proteins are crucial for inner ear development, but whether Id mutations affect middle ear function remains unknown. In this study, we obtained Id1−/−; Id3+/− mice and Id1+/−; Id3−/− mice and carefully examined their middle ear morphology and auditory function. Our study revealed a high incidence (>50%) of middle ear infection in the compound mutant mice. These mutant mice demonstrated hearing impairment starting around 30 days of age, as the mutant mice presented elevated auditory brainstem response (ABR) thresholds compared to those of the littermate controls. The distortion product of otoacoustic emission (DPOAE) was also used to evaluate the conductive function of the middle ear, and we found much lower DPOAE amplitudes in the mutant mice, suggesting sound transduction in the mutant middle ear is compromised. This is the first study of the middle ears of Id compound mutant mice, and high incidence of middle ear infection determined by otoscopy and histological analysis of middle ear suggests that Id1/Id3 compound mutant mice are a novel model for human otitis media (OM).